Legends and Myths of Online Testing: The Truth is Out There - V. Yu. Grigorev; S. E. Novikova (Управленческое консультирование, 2020)
The article discusses the prospects of the remote format for assessing competencies through a comparative analysis with the development of classical chess, concludes that it is necessary to rethink the role and place of online testing.